3D flexible hydrogen evolution electrodes with Se-promoted molybdenum sulfide nanosheet arrays. Issue 14 (26th January 2016) - Pu, Zonghua; Wei, Shiyong; Chen, Zhibao; Mu, Shichun
Abstract : Se-promoted molybdenum sulfide nanosheet arrays supported on carbon cloth are developed as a novel electrocatalyst for hydrogen evolution reaction. Abstract : Developing high-efficiency and stable catalysts from earth-abundant elements for the hydrogen evolution reaction (HER) is essential for renewable energy conversion. In this work, Se-promoted molybdenum sulfide nanosheet arrays supported on flexible carbon cloth (Se–MoS2 /CC) have been successfully synthesized and explored for the first time as a 3D hydrogen evolution cathode. Without any active process, the Se–MoS2 /CC electrode exhibits greatly enhanced activity with a smaller Tafel slope (63 mV dec −1 ) and a higher exchange current density (0.16 mA cm −2 ) than the pristine MoS2 /CC one (79 mV dec −1 and 0.1 mA cm −2 ). The overpotentials needed to attain the current densities of 10 and 100 mA cm −2 are merely 127 and 218 mV, respectively. In addition, Se–MoS2 /CC maintains its high electrocatalytic activity for at least 25 h in acidic media.